A range-gated imaging flash Lidar based on the adjacent frame difference method. (June 2021) - Tian, Zhaoshuo; Yang, Gang; Zhang, Yanchao; Cui, Zihao; Bi, Zongjie
Highlights: Adjacent frame difference method for the range-gated imaging lidar. Thresholding the intensity difference between two adjacent frames. Two range images can be obtained by the front and back edges of the range gate. Improve the image quality by front and back edge images processing. Abstract: In this paper, we proposed an adjacent frame difference (AFD) method to reconstruct 3-dimension (3D) images for range-gated flash imaging Lidars. In this novel method, the range information of the target is obtained by thresholding the intensity difference between two adjacent frames from the intensified charge-coupled device (ICCD), which is triggered by the range-gate signals with step delays. To verify the feasibility of this method, a target building at a distance of 2.4 km was measured by our self-developed range-gated flash imaging Lidar based on AFD method. The real-time 3D images of the target were reconstructed at the front and back edges of the range gate, respectively. The difference of the range information from the front and back edges can be used to denoise the target image and improve image clarity. Compare to the trapezoid-range-intensity profile method and the triangular-range-intensity profile method, this method needn't strict correlation between the range-gate and laser pulse widths, and has many advantages such as fast imaging speed, large imaging range, and simple data processing. The theoretical analysis and experimental results indicate the range-gated flash imaging Lidar using AFD method has the high practicality and wide applications.